The Samaritan Pentateuch / Volume 3 Leviticus / edited by Stefan Schorch ; in collaboration with Evelyn Burkhardt and Ramona Fändrich - Burkhardt, Evelyn; Fändrich, Ramona; Schorch, Stefan (The Samaritan Pentateuch a critical Editio Maior, 2018)
A critical edition of the Samaritan Pentateuch is one of the most urgent desiderata of Hebrew Bible research. The present volume on Leviticus is the first out of a series of five meant to fill this gap. It provides a diplomatic edition of the five books of the Samaritan Torah, based on the oldest preserved Samaritan manuscripts.Throughout the entire work, the Samaritan Hebrew text as gathered from 30 different manuscripts is compared with further Samaritan witnesses (esp. the Samaritan Targum, the Samaritan Arabic translation, and the oral Samaritan reading tradition) as well as with non-Samaritan witnesses of the Pentateuch, especially the Masoretic text, the Dead Sea Scrolls, and the Septuagint, creating an indispensable resource and tool not only for those working with the Samaritan Pentateuch, but for any scholar interested in textual criticism of the Hebrew Bible in general, and particularly the Pentateuch.